DOMESTIC VIOLENCE AGAINST WOMEN IN NIGERIA: A PHILOSOPHICAL STUDY - Chris O. Abakare (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
Family, apart from providing security and emotional support should provide the most secure environment for an individual to grow. However, domestic violence is largely evident in the Nigeria families and societies. Although, women are worshipped as deities at home in some cultures in Nigeria, they are also treated as second class members of the family. This is largely due to the patriarchal nature of the Nigerian society. The essence of this work is to investigate domestic violence against woman in Nigeria. This work discovers that the lack of physical power leads to general timidity in women. This work discovers that domestic violence is perpetrated by family members against women in the family, ranging from single assault to aggravated physical battery, threats, intimation, coercion, stalking, humiliating verbal use, forcible or unlawful entry, sexual violence, marital rape, dowry and even female genital mutilation. This work is of the opinion that domestic violence bluntly trips women of their most basic human rights, the right to safety in their homes and community and should be discourage.Family, apart from providing security and emotional support should provide the most secure environment for an individual to grow. However, domestic violence is largely evident in the Nigeria families and societies. Although, women are worshipped as deities at home in some cultures in Nigeria, they are also treated as second class members of the family. This is largely due to the patriarchal nature of the Nigerian society. The essence of this work is to investigate domestic violence against woman in Nigeria. This work discovers that the lack of physical power leads to general timidity in women. This work discovers that domestic violence is perpetrated by family members against women in the family, ranging from single assault to aggravated physical battery, threats, intimation, coercion, stalking, humiliating verbal use, forcible or unlawful entry, sexual violence, marital rape, dowry and even female genital mutilation. This work is of the opinion that domestic violence bluntly trips women of their most basic human rights, the right to safety in their homes and community and should be discourage. Keywords:Domestic violence, Women, Patriarchy, Nigeria.